Spin‐State Variations of Iron(III) Complexes with Tetracarbene Macrocycles. Issue 15 (11th February 2019) - Schremmer, Claudia; Cordes (née Kupper), Claudia; Klawitter, Iris; Bergner, Marie; Schiewer, Christine E.; Dechert, Sebastian; Demeshko, Serhiy; John, Michael; Meyer, Franc
Abstract: Starting from their six‐coordinate iron(II) precursor complexes [L 8R Fe(MeCN)] 2+, a series of iron(III) complexes of the known macrocyclic tetracarbene ligand L 8H and its new octamethylated derivative L 8Me, both providing four imidazol‐2‐yliden donors, were synthesized. Several five‐ and six‐coordinate iron(III) complexes with different axial ligands (Cl −, OTf −, MeCN) were structurally characterized by X‐ray diffraction and analyzed in detail with respect to their spin state variations, using a bouquet of spectroscopic methods (NMR, UV/Vis, EPR, and 57 Fe Mößbauer). Depending on the axial ligands, either low‐spin ( S= 1/2) or intermediate‐spin ( S= 3/2) states were observed, whereas high‐spin ( S =5/2) states were inaccessible because of the extremely strong in‐plane σ‐donor character of the macrocyclic tetracarbene ligands. These findings are reminiscent of the spin state patterns of topologically related ferric porphyrin complexes. The ring conformations and dynamics of the macrocyclic tetracarbene ligands in their iron(II), iron(III) and μ‐oxo diiron(III) complexes were also studied. Abstract : Spin‐state patterns : Reminiscent of iron(III) porphyrinates and identified by characteristic spectroscopic signatures, ferric complexes of macrocyclic tetracarbenes were observed to adopt either low‐spin ( S= 1/2) or intermediate‐spin ( S= 3/2) states, depending on the number and field strength of axial ligands. Carbene ligation, however, rendered a high‐spin ( S= 5/2) state inaccessible. Fe II /Fe III redox potentials and macrocycle ring dynamics were modulated by peripheral substituents at the equatorial tetracarbene scaffold.